Serial quantitative coronary angiography (QCA) in the assessment of transplant coronary artery disease (TxCAD) - Barańska-Kosakowska, Anna; Hawranek, Michał; Gąsior, Mariusz; Spatuszko, Artur; Przybylski, Roman; Zakliczyński, Michał; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Background : Transplant coronary artery disease (TxCAD) is one of the major causes of late death following orthotopic heart transplantation (OHT). Aim : The objective of this study was to compare qualitative coronary angiography with quantitative coronary angiography (QCA) in the assessment of TxCAD in a population of heart transplant recipients, who survived at least 5 years after transplantation and were followed up to 15 years. Material and methods : From 1991 to 2000, 164 coronary angiograms (CAG) from 82 recipients were reviewed to determine the prevalence and severity of TxCAD (2 CAG for each patient). The time from first to second assessed CAG was 47 ±20 months. TxCAD onset was defined as any narrowing seen at coronary angiography and severe TxCAD was recognized when coronary events including myocardial infarction, coronary revascularizations and coronary death, were registered in follow-up. Changes in percent diameter stenosis (DS) and minimum lumen diameter (MLD) were measured by QCA. Results : TxCAD was recognized in 57 recipients and severe disease occurred in 30 of them. The cumulative incidence of TxCAD assessed angiographically was 24% 5 years after OHT and 50% 10 years after OHT. QCA analysis revealed a significant decrease loss of MLD, which was greater in patients with TxCAD compared to patients without TxCAD (–0.18 ±0.57 mm vs. –0.06 ±0.37 mm, p = 0.02) and in patients who developed severe TxCAD compared to patients with mild TxCAD (–0.31 ±0.72 mm vs. –0.04 ±0.30 mm, p = 0.005). Progression of DS was also greater in patients with TxCAD compared to patients without TxCAD (13.63 ±22.48% vs. –1.40 ±10.01%, p < 0.001) and comparing to patients with a severe and mild form of the disease (27.19 ±26.24% vs. 2.21 ±8.93%, p < 0.001). Significant differences in QCA measures related to the onset of TxCAD were seen in proximal segments of the left anterior descending coronary artery and right coronary artery compared to significant differences in QCA measures related to severity of TxCAD, which were present also in medium and distal segments of these arteries. Conclusions: Changes of the minimum lumen diameter and diameter stenosis were related to onset of TxCAD and “hard” coronary events, including coronary death. QCA measures may be better surrogate end points for severe TxCAD according to significant differences in distal segments of coronary arteries.